Pengaruh Pelatihan Tenaga Pengajar Terhadap Produktivitas Kerja Pada Griya Quran Darul Mahabbah Kota Pangkalpinang - Aslamiah, Suaibatul; Syahrinullah, Syahrinullah (LPPM Universitas Muhammadiyah Mamuju, 2022)
Griya Quran Darul Mahabah city of Pangkal Pinang is one of the Quranic education programs for the younger generation with the aim of providing understanding and deepening the knowledge of the Quran. Training is an activity used in institutions to acquire and increase teaching competence. The aim of the research is to find out and analyze the effect of the level of education and training of teachers on work productivity at the Griya Quran Darul Mahabah Islamic Boarding School in Pangkal Pinang City. The research method used is a qualitative method. The data analysis technique that will be used in this research is obtained from the results of interviews, field notes, and documentation, by organizing data into categories, describing them into units, synthesizing, compiling into patterns choosing which ones are important and which ones will be learn, and make conclusions so that it is easily understood by oneself and others. The results obtained from this research show that there is a positive